Innate immunity and cellular senescence: The good and the bad in the developmental and aged brain. Issue 3 (1st February 2018) - Santoro, Antonietta; Spinelli, Chiara Carmela; Martucciello, Stefania; Nori, Stefania Lucia; Capunzo, Mario; Puca, Annibale Alessandro; Ciaglia, Elena
Abstract: Ongoing studies evidence cellular senescence in undifferentiated and specialized cells from tissues of all ages. Although it is believed that senescence plays a wider role in several stress responses in the mature age, its participation in certain physiological and pathological processes throughout life is coming to light. The "senescence machinery" has been observed in all brain cell populations, including components of innate immunity (e.g., microglia and astrocytes). As the beneficial versus detrimental implications of senescence is an open question, we aimed to analyze the contribution of immune responses in regulatory mechanisms governing its distinct functions in healthy (development, organogenesis, danger patrolling events) and diseased brain (glioma, neuroinflammation, neurodeneration), and the putative connection between cellular and molecular events governing the 2 states. Particularly this review offers new insights into the complex roles of senescence both as a chronological event as age advances, and as a molecular mechanism of brain homeostasis through the important contribution of innate immune responses and their crosstalk with neighboring cells in brain parenchyma. We also highlight the impact of the recently described glymphatic system and brain lymphatic vasculature in the interplay between peripheral and central immune surveillance and its potential implication during aging. This will open new ways to understand brain development, its deterioration during aging, and the occurrence of several oncological and neurodegenerative diseases.